Predictors of Disease Control After Endoscopic Sinus Surgery Plus Long-Term Local Corticosteroids in CRSwNP. Issue 1 (January 2021) - De Corso, Eugenio; Settimi, Stefano; Tricarico, Laura; Mele, Dario Antonio; Mastrapasqua, Rodolfo Francesco; Di Cesare, Tiziana; Salvati, Antonio; Trozzi, Lucrezia; De Vita, Carla; Romanello, Matteo; Paludetti, Gaetano; Galli, Jacopo
Background: in the era of new biological agents it is important to identify patients who may benefit from conventional therapies such as endoscopic sinus surgery (ESS) plus long-term local corticosteroids from those with patterns of inflammation that are more difficult to control post-operatively and who may benefit from other therapies. Objective: determine if preoperative assessment of type and grade of inflammation and clinical factors can predict disease control with ESS plus long-term local corticosteroids in chronic rhinosinusitis with nasal polyps (CRSwNP). Methods: Eighty patients treated with ESS plus mometasone-furoate 200 μg BID for CRSwNP and followed for at least 1 year were enrolled (November 2017–December 2018) in this prospective observational study. Type and grade of inflammation were evaluated preoperatively by nasal cytology. Based on cellular pattern, patients were grouped as neutrophilic (n = 20), eosinophilic (n = 38), or mixed eosinophil-neutrophilic (n = 22). SNOT-22 and Lund-Kennedy Endoscopic Score were evaluated at baseline and at 3, 6, 9, and 12 months after surgery and used to define disease control. Results: The cumulative probability of remaining free of significant modification of endoscopic score (Lund-Kennedy Endoscopic Score >2) at 3, 6, 9, and 12 months was 0.84, 0.76, 0.71, and 0.68, respectively. At 12-month postoperative evaluation good disease control was observed in 54 of 80 patients (67.5%). Compared to those with good post-operative disease control, those with poor control had a significantly higher pre-operative mean count of eosinophils and neutrophils (p < 0.05). The preoperative inflammatory pattern was associated with relative risk of poor control: neutrophilia (RR: 3.10; CI:1.24–7.71), eosinophilia (RR:8.42; CI:2.72–15.12), and mixed eosinophilic and neutrophilic (RR:25.11; CI:19.41–30.01). We also confirmed that asthma, allergy, blood eosinophilia, and ASA triad could predict poor control. Conclusions: The type and load of inflammation evaluated preoperatively and selected clinical factors can predict poor control of CRSwNP treated with ESS and local corticosteroids.